Leptomeningeal Metastases in Patients with NSCLC withEGFRMutations. Issue 11 (November 2016) - Li, Yang‐Si; Jiang, Ben‐Yuan; Yang, Jin‐Ji; Tu, Hai‐Yan; Zhou, Qing; Guo, Wei‐Bang; Yan, Hong‐Hong; Wu, Yi‐Long
ABSTRACT : Introduction : Leptomeningeal metastases (LM) have increased in patients with NSCLC, and prognostic factors and outcomes for LM with EGFR gene mutations have not been well studied. Methods : We retrospectively analyzed patients with lung cancer from January 2011 to June 2015 at our institute. Treatments and clinical outcomes of LM were reviewed. Results : LM were diagnosed in 184 (3.4%) of 5387 patients with lung cancer. Patients with LM harboring EGFR mutations (9.4%) were significantly more frequent than those with wild‐type EGFR (1.7% [ p < 0.001]). The median overall survival (OS) after LM was 8.7 months (95% confidence interval [CI]: 7.3–10.1). Among the 109 patients with common EGFR mutations, the 88 patients who received tyrosine kinase inhibitor (TKI) therapy demonstrated longer OS than those who did not (10.0 months versus 3.3 months [ p < 0.001]), but 42 patients who underwent whole brain radiotherapy (WBRT) did not show longer OS than those without WBRT, and a combination of WBRT and TKIs did not add any survival benefit beyond that in patients receiving only TKIs. A multivariate analysis indicated that TKI therapy ( p < 0.001, hazard ratio = 0.218) was an independent predictor of favorable survival, whereas poor Eastern Cooperative Oncology Group performance status ( p < 0.001, hazard ratio = 3.657) was a predictor of poor survival. Conclusions : LM were much more frequent in patients with NSCLC harboring EGFR mutations. EGFR TKIs were the optimal treatment for LM, and active treatment with WBRT did not prolong OS for EGFR ‐mutated patients.